Evidence of mobile health integration into primary health care systems for better maternal mental health in LMIC during COVID-19 pandemic - Review - Jabeen , Rawshan; Mubarak Jabeen Salman,; Ibtisaam Qazi , (Journal of the Pakistan Medical Association, 2022)
Mental illnesses are prevalent worldwide, especially in the underdeveloped countries of the South Asian region, particularly in women, where they largely remain unaddressed. Evidence from the South Asian region indicates that there is a high burden of mental disorders in vulnerable populations such as pregnant women. Mental health problems during pregnancy and in the postpartum period are twice as common in LMICs as compared to HICs. Interventions delivered by community health workers (CHWs) in many health delivery and promotive initiatives have played a vital role in improving mental health. CHW-based interventions are cost-effective, efficient and acceptable for the local people and can strengthen the overall health system. This review aimed to explore integration of maternal mental health into existing maternal, newborn and child health (MNCH) programs so that delivery of mental health interventions can be done alongside MNCH interventions. ---Continue